The Investigation of Students’ Knowledge on a Novel Learning Strategy: What is Interesting about Blended Learning for EFL University Students? - Riska Yuliana; Marwa Marwa; Budianto Hamuddin (Utamax : Journal of Ultimate Research and Trends in Education, 2020)
This research aimed at exploring students’ interest and knowledge in blended learning context at English Education Department in Universitas Lancang Kuning (Unilak). This descriptive quantitative research involved 27 out of 135 students as the samples as they are part of a class that uses blended learning actively through their entire semester. These 27 students were selected by using random sampling technique from fourth, sixth, and eight semester in regular class. The questionnaire used as the main instrument to collect the data. The data analyzed descriptively in term of mean and standard deviation then interpreted descriptively. The result of the findings revealed that the majority of students’ have High level of students’ interest and knowledge in blended learning context. It was probed by their mean score, interest students’ score 3.71 and the students’ knowledge score 3.67. The standard deviation to interest was 6,83 and knowledge was 5.28. This is means that the blended learning which employed during these 2 years seems in a high interest and knowledge level among the students at English Language Education Department.